2022
DOI: 10.3389/fimmu.2022.955581
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture attenuates surgical pain-induced delirium-like behavior in mice via remodeling gut microbiota and dendritic spine

Abstract: Surgical pain is associated with delirium in patients, and acupuncture can treat pain. However, whether electroacupuncture can attenuate the surgical pain-associated delirium via the gut–brain axis remains unknown. Leveraging a mouse model of foot incision-induced surgical pain and delirium-like behavior, we found that electroacupuncture stimulation at specific acupoints (e.g., DU20+KI1) attenuated both surgical pain and delirium-like behavior in mice. Mechanistically, mice with incision-induced surgical pain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…A battery of behavioral tests was recently utilized to assess delirium-like behavior in a mouse model, facilitating preclinical delirium studies (Chen et al 2022 ; Yang et al 2022 ). We assessed mouse locomotor activity using the OFT and found significant impairment after cardiac surgery, in contrast to previous laparotomy-based studies (Li et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…A battery of behavioral tests was recently utilized to assess delirium-like behavior in a mouse model, facilitating preclinical delirium studies (Chen et al 2022 ; Yang et al 2022 ). We assessed mouse locomotor activity using the OFT and found significant impairment after cardiac surgery, in contrast to previous laparotomy-based studies (Li et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the need for an ideal animal model to study postoperative delirium‐like behavior, our lab has developed an animal behavioral test battery. This battery includes natural behaviors such as buried food and an open‐field test to evaluate attention and awareness, as well as a learned behavior test (Y maze) to assess cognition 54,56–58,78 . These tests evaluate behaviors in mice that rely on intact attention, organized thinking, and consciousness.…”
Section: Discussionmentioning
confidence: 99%
“…This battery includes natural behaviors such as buried food and an open-field test to evaluate attention and awareness, as well as a learned behavior test (Y maze) to assess cognition. 54,[56][57][58]78 These tests evaluate behaviors in mice that rely on intact attention, organized thinking, and consciousness. Notably, we have demonstrated that aged mice display greater susceptibility to these behaviors after anesthesia/surgery compared to adult mice, 56 which parallels the clinical observation of a higher incidence of postoperative delirium in senior patients relative to adult patients.…”
Section: Kim Et Al Reported That Ad Tg Mice Had Increased Amounts Ofmentioning
confidence: 99%
“…Animal studies have also confirmed that acupuncture can reduce cognitive impairment and the associated pathological changes after various types of surgery. Yang et al [ 47 ] found that EA stimulation at specific acupoints (e.g., DU20 + KI1) attenuated both surgical pain and delirium-like behavior in mice by a potentially important gut-brain interactive mechanism. Further studies showed that EA stimulation at specific acupoints could prevent neuroinflammation by reducing the activation of microglia at the spinal cord, somatosensory cortex, and hippocampus, and also affect the vagal-adrenal axis in mice.…”
Section: Potential Mechanisms Of Acupuncture Against Podmentioning
confidence: 99%